2018
DOI: 10.1016/j.envint.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Residential landscape as a predictor of psychosocial stress in the life course from childhood to adolescence

Abstract: Residential greenness in proximity to a child's residence might result in a better childhood emotional status, whereas poorer emotional status and behavioral problems (hyperactivity problems) were seen with residential and industrial areas and increased traffic density in proximity to a child's home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 41 publications
2
47
0
1
Order By: Relevance
“…We explored mediation analysis to explore this but failed to detect a mediation role of physical activity. Additionally, greenness was also associated with psychosocial stress, reduced noise exposure, and greater and more diverse microbial exposure, all of them might influence glucose homeostasis and the development of diabetes mellitus [9,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…We explored mediation analysis to explore this but failed to detect a mediation role of physical activity. Additionally, greenness was also associated with psychosocial stress, reduced noise exposure, and greater and more diverse microbial exposure, all of them might influence glucose homeostasis and the development of diabetes mellitus [9,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review identified nine studies of associations of environmental noise on cognition [39,48,[84][85][86][87][88][89][90]. Studies examined child and adult samples.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Two other studies known to the authors were also added [94,95], along with another recent conference paper [93]. Six studies were excluded after data extraction (Appendix A.2) which included two studies which reported experimental studies [84,85]; one that reported on mental health and not cognition and had already been identified in the search for mental health [39]; one which did not report on noise exposure per se [89], and another study which reported an ADHD outcome, which was moved to the mental health review [48]. One study reported on attitudes to noise within the school and did not report a cognitive outcome [90].…”
Section: Grade Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of the gut microbiota is affected by exposure to environmental pollutants and is associated with weight in later life [10]. Children with reduced access to greenspace report greater levels of anxiety and sadness, and this tracks into adolescence [11], which could lead to adaptations in appetite and energy regulation [12].…”
Section: Introductionmentioning
confidence: 99%